The Effect of Reciprocal Peer Tutoring Strategy to Students’ Mathematics Performance - Mastura S. Abdulkarim; Datu Ben M. Maon; Romnie A. Quiray; Faiza M. Abdul Latip (RIRAI Publisher, 2022)
This study focused on the effect of reciprocal peer tutoring strategy in teaching rational algebraic expressions to the mathematics performance of the Guindulungan National High School students. There forty (40) Grade 8 students who were randomly selected as the subjects of the study. A Quasi-experimental research design was employed in this study. Pre-test and post-test questionnaire on rational algebraic expressions was used as the main instrument of the study. Quantitative analysis on both pre-test and post-test scores of the students were made using this method. The simple frequency and percentage counts were used to analyze the students’ performance before and after the reciprocal peer tutoring strategy was introduced. t-test was utilized to determine the significant difference between the students’ performance in mathematics before and after the reciprocal peer tutoring strategy. This test was set at 5% level of significance. The minimum t-value of 1.665 was used to determine the significance of the test. The results revealed that there is a significant increase in the students’ mathematics performance in learning rational algebraic expressions using reciprocal peer tutoring strategy. This means that reciprocal peer tutoring strategy is effective in increasing students’ mathematics performance.